Reformulating Progressive Fiqh of Talak (Divorce): A Contemporary Study of the Principle of Making Divorce More Difficult in SEMA No. 1 of 2022 for Women's Protection - Laras Shesa; Muhammad Abu Dzar; Elkhairati; Henny Septia Utami (Metro Islamic Law Review)
This study aims to analyze the reformulation of progressive fiqh of Talak (divorce), with a focus on SEMA No. 1 of 2022, which emphasizes the principle of making divorce more difficult in the interest of protecting women. In the context of Islamic law, divorce has often been considered a unilateral right controlled by the husband, potentially neglecting the rights of women. SEMA No. 1 of 2022 was introduced as a response to this issue, offering a fairer and more just approach for all parties involved. This research employs a library research method, reviewing legal literature, official documents, as well as the views of legal scholars and practitioners regarding the implementation of this policy. The analysis results show that the reformulation of the fiqh of divorce in SEMA No. 1 of 2022 provides a better platform for protecting women's rights in divorce proceedings, including encouragement for mediation and peaceful dispute resolution. Furthermore, this study identifies challenges in the application of this principle on the ground, including cultural and social resistance. This research is expected to contribute to the development of family law in Indonesia that is more responsive to the needs of women, as well as to raise awareness of the importance of justice for all parties in the context of divorce. This study serves as an important reference for further research on fiqh of divorce and women's protection policies within the framework of contemporary Islamic law.